Institutional sources of legitimacy in multistakeholder global governance at ICANN - Jongen, Hortense; Scholte, Jan Aart (Regulation & governance, 2024)
This article provides a novel systematic exploration of ways and extents that institutional characteristics shape legitimacy beliefs toward multistakeholder global governance. Multistakeholderism is often argued to offer institutional advantages over intergovernmental multilateralism in handling global problems. This study examines whether, in practice, perceptions of institutional purpose, procedure, and performance affect legitimacy assessments regarding this form of global governance. The analysis focuses on the Internet Corporation for Assigned Names and Numbers (ICANN), one of the largest and most institutionally developed global multistakeholder arrangements. Evidence comes from a mixed‐methods survey of 467 participants in ICANN. We find that this representative sample accords high importance in principle to many institutional features, and also rates the actual institutional operations of ICANN quite highly on various counts. Moreover, many institutional characteristics associate significantly with participants' legitimacy beliefs toward ICANN. However, not all institutional qualities have this significance, and the relevance of individual‐ and societal‐level circumstances indicates that institutional sources do not provide a full explanation of legitimacy. The article contributes refinements to theory of legitimacy in global governance; demonstrates the value of mixed‐methods survey work in this field; supplies unique original data and analysis; and identifies implications for the politics of (de)legitimation around multistakeholderism.